PERLINDUNGAN HUKUM TERHADAP MEREK PERDAGANGAN BARANG DAN JASA - Syahriyah Semaun (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
This paper aims to provide legal protection to the brand in the trade of goods and services. It is based on legislation specifically relating to brands, namely Law No. 15 of 2001, and legislation related to the brand. With the growing importance of this brand, the brand needs to be placed on the legal protection as an object against him over the rights of individuals or legal entities. Law No. 15 of 2001 aims to give more legal protection for rights holders of trademarks. To ensure the legal protection of brand in the process of trade in goods and services, then the owner of the brand is expected to register a trademark in order to obtain legal certainty.